THE INFLUENCE OF LEADERSHIP STYLE AND WORK STRESS ON EMPLOYEE PERFORMANCE IN HUTA BAYU RAJA SUB-DISTRICT OFFICE - Christina Natalia Hutagalung; Jefry Nando Ginting; Adrian K. Tarigan (Universitas Efarina, 2019)
Study This aim For see Influence of Leadership Style and Stress Work on Employee Performance Good in a manner Partial nor simultaneously at the Huta Bayu Raja District Office . Type research used _ is quantitative . Population in study This is employee office sub-district head Huta Bayu Raja, totaling 31 people and determination amount sample in study This that is with make population become sample , however No including Head Camat , the reason that became subject influence in research This is Head Camat . So that sample study This amounted to 30 respondents . Research data sources This is primary data with using research instruments form questionnaire . Method data collection used is survey research . Study This use analysis multiple linear regression For analysis statistics and regression models has tested especially formerly in the assumption test classic . Research results state that testing in a manner Partial Demonstrate Leadership Style influential positive significant on Employee Performance at the Huta Bayu Raja District Office , and testing in a manner Partial show stress Work influential negative significant on Employee Performance at the Huta Bayu Raja District Office . kindly together Leadership Style and Stress Work influential significant on Employee Performance at the Huta Bayu Raja District Office . In t test count 2,923 > 1,703 t table , with mark significant 0.007 <0.05 stated there is influence significant between style leadership to performance employee at Huta Bayu Raja District Office . In t test count -0.773 < 1.703 t table , with mark significant 0.446 > 0.05 declared No exists influence between stress Work to performance employee at Huta Bayu Raja District Office . In the f test count 4.461 > 3.32f table , with mark significant 0.021 < 0.05 stated in a manner together there is influence significant between style leadership and stress Work to performance employee at Huta Bayu Raja District Office . The leadership style used in study This is style leadership democratic , where leader camat always involve employee in every discussion taking decision as well as leaders who don't egotistical and exemplary .